Impact of Financial Deepening, Energy Consumption and Total Natural Resource Rent on CO2 Emission in the GCC Countries: Evidence from Advanced Panel Data Simulation - Saqib, Najia; Duran , Ivan A.; Hashmi, Nazia (International Journal of Energy Economics and Policy, 2022)
The study examined the dynamic nexus between financial deepening, natural resource rent, nonrenewable-energy and renewable-energy consumption and CO2 emission by using a dataset of six GCC countries (UAE, Saudi Arabia, Qatar, Oman, Kuwait and Bahrain) from 1993 to 2019. For estimation, study applying second-generation panel unit root, cointegration and long-run estimation tests for robust and efficient results. The study confirms the presence of cross-sectional dependency while economic expansion and nonrenewable-energy contribute to CO2 emissions, financial deepening and renewable-energy consumption have a significant impact on reducing environmental degradation. Furthermore, the Dumitrescu-Hurlin causality test reveals a statistically significant bidirectional correlation between financial deepening, consumption of nonrenewable-energy and renewable-energy and CO2 emission. In light of these findings, a number of policy recommendations are provided to help the GCC countries overcome on CO2 emissions while promoting economic growth.